Peptidoglycan synthesis and turnover in cell division mutants of Agmenellum. - Dickens, B F (1976)
The synthesis and turnover of peptidoglycan in Agmenellum quadruplicatum was investigated using D-[U-14C]alanine followed by proteolytic digestion. The rate of turnover of alanine in the peptide portion of the peptidoglycan was measured in strain BG-1 and in two division mutants of this strain: one was blocked in cell separation; and the other was a low-temperature, conditional cell division mutant. The peptide portion of peptidoglycan turned over in all three strains tested, but no correlation was observed between septum formation or cell separation and the rate of turnover. Peptidoglycan synthesis was measured during induced division in snake forms of strain SN-29. A stimulation of peptidoglycan synthesis was observed during the period of cross-wall formation, even in the absence of new protein synthesis. Thus in A. quadruplicatum, cross-wall synthesis is accompanied by a stimulation of peptidoglycan synthesis.